Vladimir Putin, Twenty Years On: Russia’s Foreign Policy - Freire, Maria Raquel (2020)
This article touches upon the main dynamics in Russian foreign policy since Vladimir Putin came to power in 2000. Following a Constructivist approach to the analysis of foreign policy, the article positions this study at the intersection of domestic processes and external relations, as well as understanding foreign policy as a combination of material and ideational aspects. The discursive practices that drive foreign policy shaping and making are the result of social interaction, and thus, of the combination of these elements, in different formats and weights. Three main dimensions in Russia’s foreign policy course are identified, namely a normative one, defining the guiding principles for foreign policy shaping, the status dimension as the power-alignment underlining foreign policy making, and an identity-driven dimension, ontologically characterizing foreign policy. These three dimensions of analysis are co-constitutive and reinforce each other at different moments and in distinct configurations. The article concludes that Russian foreign policy in the last twenty years has kept its main end-goal quite stable — great power status, — what has changed have been the means — and ways of doing — to achieve this, both regarding a more assertive foreign policy, and increased pressure for revising the international order, attributing Russia the label of a revisionist power in the international system.